Coastal sedimentation and topographic changes in the Mataram Plain, Lombok (Indonesia) following the 1257 CE eruption of Samalas volcano - Malawani, Mukhamad Ngainul (John Wiley and Sons Ltd, 2023)
The 1257 CE eruption of Samalas volcano, Indonesia, buried the entire island of Lombok beneath various thicknesses of pyroclastic material during this Volcanic Explosivity Index (VEI) 7 event. This study aims to reconstruct the paleo-topography of western Lombok before the Samalas eruption in 1257 CE and analyse the sedimentation processes that led to its landscape evolution over the last 700 years. Stratigraphic data were collected from various surveys, such as outcrops, coring, drilling, hand auger and wells observation. Electrical resistivity tomography (ERT) measurements were performed to complement the stratigraphic data. A combination of stratigraphy, ERT and topographic data from various sources (topographic map, Digital Elevation Model Nasional DEMNAS and Real Time Kinematic RTK measurement) is employed to determine the depth of the paleo-surface. Topographic modelling was performed by subtracting the delta-DEM (DDEM) from the current-DEM (CDEM). The result of this operation is a paleo-DEM, which is used to reconstruct the paleo-hydrographic features such as shoreline positions and river channels. Modelling results demonstrate that the relief has not been significantly modified, except in lowland areas, which is the sediment accumulation zone. River channels have experienced minor changes, except for the location of the river mouth and the degree of meandering. Significant changes occurred at the shoreline that has prograded by approximately 1.6 km during the last 700 years. A schematic model is built to illustrate the evolution processes of the study area, consisting of the pre-eruption condition, the immediate post-eruption condition and development of the current condition. This model further develops the previously proposed model with a higher resolution and simultaneously revises the estimated boundary of the pyroclastic density current (PDC) deposit from previous work. © 2023 John Wiley & Sons Ltd.